Uncommon understanding: Development and disorders of language comprehension in children, classic edition - Bishop, D (Taylor and Francis, 2014)
This is a Classic Edition of Dorothy Bishop's award-winning textbook on the development of language comprehension, which has been in print since 1997, and now includes a new introduction from the author. The book won the British Psychological Society book award in 1999, and is now widely seen as a classic in the field of developmental language disorders.